The impact of paternal support on the success of exclusive breastfeeding among lactating mothers in Ado-Odo/Ota local government area of Ogun State - Jelili A. QUADRI; Yetunde J. OSINOWO; Lyanu C. ALAGBE; Tobi I. AKINREMI; Bilikisu T. EDUN (Nutrition & Santé)
Introduction. Exclusive breastfeeding (EBF) is crucial for infant health, but socio-cultural factors, particularly paternal support, influence its success. Objective. This study examined the impact of paternal support on EBF among lactating mothers in Ado-Odo/Ota Local Government Area, Ogun State, Nigeria. Population and Methods. A descriptive cross-sectional survey was conducted among 338 participants, including lactating mothers with infants aged 0–6 months and their spouses. Data were collected using a structured questionnaire, and analyzed using SPSS version 26. Results. Forty-five % of fathers were aware of EBF, but only 29% correctly identified the recommended six-month duration. While 50% believed in the benefits of EBF, 33% viewed breastfeeding as solely the mother responsibility. Only 19% had received formal breastfeeding edu-cation. Despite this, 41% were willing to participate in EBF awareness programs. Paternal support was observed in 58% of cases, with financial assistance (70%) being the most common, followed by emotional encouragement (55%), and household assistance (45%). However, only 20% of fathers attended postnatal visits. EBF coverage in the study area was 26%, with early discontinuation attributed to work constraints (45%), percei-ved insufficient breast milk (35%), and lack of partner support (30%). Significant positive correlations were found between paternal emotional support and EBF duration (p=0.001, r=0.47), and financial support and EBF duration (p=0.005, r=0.38). Conversely, work schedule limitations affected negatively EBF duration (p=0.012, r=-0.35). Cultural beliefs also played a role, with 55% of respondents (both parents) perceiving breastfeeding as solely the mother responsibility. Conclusion. These findings underscore the need for targeted interventions to enhance paternal engagement in EBF. Recom-mendations include increased male-targeted breastfeeding education, workplace policies supporting lactating mothers and their spouses, and community awareness campaigns addressing cultural barriers. Strengthening policies to encourage father-inclusive maternal health programs can significantly improve EBF rates and infant health outcomes.